High-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane as well as preparation method and application thereof
By introducing a functional group-modified mesoporous SiO2 nanoparticle intermediate layer into the nanofiltration membrane, the problem of easy degradation of polyamide nanofiltration membranes under acidic conditions was solved, and high flux, high rejection rate and acid resistance nanofiltration membrane performance were achieved.
Patent Information
- Application Number
- CN202511026794.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-24
- Publication Date
- 2025-10-31
AI Technical Summary
Existing polyamide nanofiltration membranes are prone to degradation under acidic conditions, leading to deterioration of membrane performance and limiting their application under acidic conditions. There is a lack of acid-resistant nanofiltration membranes with high flux and high rejection rate.
A functional group-modified mesoporous SiO2 nanoparticle intermediate layer is introduced between the base membrane and the separation layer. The mesoporous SiO2 nanoparticles modified with amino and/or trifluoropropyl groups enhance the adhesion and charge of the membrane, provide additional water channels, and hinder the permeation of acidic media, thus constructing a stable composite membrane.
It improves the permeate flux and rejection rate of nanofiltration membranes, enhances the acid resistance of membranes, and ensures stable operation in acidic environments.
Smart Images

Figure CN120860849A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanofiltration membrane technology, and in particular to a high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane, its preparation method, and its application. Background Technology
[0002] With the continuous development of new energy vehicles and the pursuit of carbon neutrality, the market size and penetration of lithium-ion batteries are constantly expanding, reducing pollutant emissions and lowering carbon emissions. However, lithium-ion batteries have a limited lifespan, and their performance degrades over time, eventually failing to meet usage requirements and becoming obsolete. Currently, the most commonly used lithium batteries on the market are lithium iron phosphate and ternary lithium batteries. The mainstream lithium battery recycling technologies include wet recycling, pyrometallurgical recycling, and direct recycling. Among these, wet recycling is widely used due to its simple operation and low energy consumption; acid leaching is the mainstream trend in wet recycling.
[0003] Nanofiltration is an important branch of membrane separation technology, offering advantages such as environmental friendliness, low cost, and ease of operation. It can effectively separate metal ions from acidic wastewater. Currently, most commercial nanofiltration membranes are polyamide nanofiltration membranes. However, the amide groups are susceptible to proton attack, causing them to degrade under acidic conditions, leading to membrane performance degradation and limiting their application in acidic environments.
[0004] Therefore, the development and preparation of nanofiltration membranes with high throughput, high rejection rate, and acid resistance remains the focus of current polyamide nanofiltration membrane research. Summary of the Invention
[0005] To address the aforementioned problems in the existing technology, this invention provides a high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane, its preparation method, and its application. This invention introduces an intermediate layer of mesoporous SiO2 nanoparticles with functional group modification between the base membrane and the separation layer, enabling the polysulfonamide acid-resistant nanofiltration membrane to possess the advantages of high flux, high rejection rate, and acid resistance.
[0006] The specific details of the invention are as follows: In a first aspect, the present invention provides a high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane, comprising a base membrane and a separation layer, and further comprising an intermediate layer located between the base membrane and the separation layer; the intermediate layer comprises functionally modified mesoporous SiO2 nanoparticles; wherein... The functional group-modified mesoporous SiO2 nanoparticles are selected from amino-modified mesoporous SiO2 nanoparticles, and / or mesoporous SiO2 nanoparticles co-modified with amino and trifluoropropyl groups.
[0007] Optionally, the amino-modified mesoporous SiO2 nanoparticles are obtained by the following preparation method: Mesoporous SiO2 nanoparticles were dispersed in an ammonia solution and mixed with a 1-10 wt% solution of 3-aminopropyltriethoxysilane. After ultrasonic stirring for 8-12 h, the solid particles were separated, washed, and dried to obtain amino-modified mesoporous SiO2 nanoparticles.
[0008] Optionally, the mesoporous SiO2 nanoparticles co-modified with amino and trifluoropropyl groups are obtained by the following preparation method: Mesoporous SiO2 nanoparticles were dispersed in an ammonia solution, and 3-aminopropyltriethoxysilane and 3,3,3-trifluoropropyltrimethoxysilane were added. After mixing evenly, the mixture was reacted at 60-80 °C for 8-12 h. The solid particles were separated, washed, and dried to obtain mesoporous SiO2 nanoparticles modified with amino and trifluoropropyl groups.
[0009] Optionally, the composition of the base film is selected from polyethylene, polypropylene, or polyacrylonitrile; The separation layer is composed of polysulfonamide.
[0010] In a second aspect, the present invention provides a method for preparing the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane described in the first aspect above, the method comprising the following steps: The base membrane was placed in NaOH solution and soaked for 2-4 hours, then transferred to an activation solution for 1-2 hours to obtain a hydrophilic base membrane. Functionally modified mesoporous SiO2 nanoparticles are dispersed in N,N-dimethylformamide to form a dispersion. One side of the hydrophilic base membrane is brought into contact with the dispersion, so that the functional groups on the surface of the functionally modified mesoporous SiO2 nanoparticles undergo a nucleophilic substitution reaction with the activated hydroxyl groups on the surface of the hydrophilic base membrane, and are fixed to the surface of the hydrophilic base membrane. After drying, a polysulfonamide acid-resistant nanofiltration membrane intermediate is obtained. One side of the intermediate with functional group-modified mesoporous SiO2 nanoparticles is fixed on the surface and then contacted with an aqueous phase containing organic amines and an organic phase containing organic sulfonyl chlorides, respectively. Through interfacial polymerization, a separation layer is formed on the surface of the intermediate, thus completing the preparation of the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane. The activation solution comprises trifluoroethanesulfonic anhydride and anhydrous pyridine, with anhydrous dichloromethane as the solvent, and the concentration of the trifluoroethanesulfonic anhydride and anhydrous pyridine is 0.1M.
[0011] Optionally, the concentration of the functional group-modified mesoporous SiO2 nanoparticles in the dispersion is 0.1~5wt%.
[0012] Optionally, the hydrophilic base film is in contact with the dispersion for 2-6 hours.
[0013] Optionally, the organic amine is selected from polyethyleneimine and / or polyacrylamide, and the concentration of the organic amine in the aqueous phase is 0.5 wt% to 3.5 wt%.
[0014] Optionally, the organic sulfonyl chloride is selected from at least one of 1,3,5-benzenetrisulfonyl chloride, 1,3,6-naphthalenetrisulfonyl chloride and isophenyl disulfonyl chloride, and the concentration of the organic sulfonyl chloride in the organic phase is 0.1wt% to 0.3wt%.
[0015] Optionally, the mesoporous SiO2 nanoparticles are obtained by the following method: Dissolve hexadecyltrimethylammonium bromide in a mixed solution of deionized water and ethanol, and adjust the pH to 10-11 by adding ammonia dropwise; Continue to slowly add tetraethyl orthosilicate to the mixed solution, stir the reaction for 2-4 h, add tricresylene and continue the reaction for 1-2 h, reflux the resulting emulsion with acidic ethanol for 10-12 h, centrifuge and collect the particles, wash and vacuum dry to obtain the mesoporous SiO2 nanoparticles.
[0016] Thirdly, the present invention provides an application of the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane described in the first aspect above, wherein the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane is used as a membrane material for membrane separation and recovery of precious metals in acidic wastewater.
[0017] Compared with the prior art, the present invention has the following advantages: This invention provides a high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane, comprising a base membrane and a separation layer, and further comprising an intermediate layer located between the base membrane and the separation layer; the intermediate layer comprises functional group-modified mesoporous SiO2 nanoparticles; wherein the functional group-modified mesoporous SiO2 nanoparticles are selected from amino-modified mesoporous SiO2 nanoparticles, and / or mesoporous SiO2 nanoparticles co-modified with amino and trifluoropropyl groups; This invention modifies the surface of mesoporous SiO2 nanoparticles with functional groups, giving them abundant amino groups and / or amino and fluorine-containing groups, providing more reaction binding sites for the subsequent bonding of mesoporous SiO2 nanoparticles with the base film, and providing higher chargeability. Functional group-modified mesoporous SiO2 nanoparticles, as an intermediate layer, can significantly change the surface charge of nanofiltration membranes, improve the rejection rate of divalent cations, and enhance the separation selectivity of monovalent and high-valent ions. Functionally modified mesoporous SiO2 nanoparticles, as an intermediate layer, can provide additional water channels, thereby increasing the permeation flux of the membrane and compensating for the low permeation flux of polysulfonamide nanofiltration membranes. Functional group-modified mesoporous SiO2 nanoparticles, as an intermediate layer, can hinder the permeation path of acidic media, delay the erosion of the membrane substrate by acid, and improve the acid resistance of the membrane. In addition, the introduction of fluorine-containing groups in the intermediate layer can not only effectively inhibit the aggregation between nanoparticles, but also provide higher acid resistance, thereby constructing a stable composite film. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 A flowchart illustrating the preparation method of the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane provided in an embodiment of the present invention is shown. Figure 2 The following are electron microscope (EM) images of the surface and cross-section of the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane provided in the embodiments of the present invention. Figure 3 The image shows an electron microscope image of the functional group-modified mesoporous SiO2 nanoparticles as the intermediate layer constructed in an embodiment of the present invention. Figure 4 A transmission electron microscope (TEM) image of the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane provided in an embodiment of the present invention is shown. Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. Based on the embodiments of the present invention, any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention. Furthermore, all other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of the present invention.
[0021] Specific experimental steps or conditions are not specified in the embodiments; they can be performed according to the conventional experimental steps or conditions described in the prior art. Reagents and other instruments used, unless otherwise specified, are all commercially available conventional reagent products. Furthermore, the accompanying drawings are merely illustrative diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the drawings denote the same or similar parts, and therefore, repeated descriptions of them will be omitted. Some block diagrams shown in the drawings are functional entities and do not necessarily correspond to physically or logically independent entities.
[0022] Techniques, methods, and devices known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and devices should be considered part of this specification.
[0023] In the description of this invention, it should be understood that the use of terms such as "first" and "second" to define components is merely for the purpose of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore should not be construed as limiting the scope of protection of this invention.
[0024] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0025] Before providing a detailed description of the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane, its preparation method, and its applications provided by this invention, it is necessary to explain the relevant technologies as follows: Chinese patent CN102794116A uses amino-modified mesoporous silica spheres as a blending agent added to an aqueous phase to react with an organic phase solution to form a separation layer. The resulting nanocomposite nanofiltration membrane improves water flux but suffers from low salt rejection. Chinese patent CN117379990A uses amino-modified MoS2 nanosheets as a monomer in a blended aqueous phase to undergo interfacial polymerization with a sulfonyl chloride-containing organic phase to prepare a polysulfonamide nanofiltration membrane. However, the resulting membrane has poor permeate flux and divalent ion rejection, and its performance deteriorates significantly after acid treatment. Chinese patent CN118807463A... Adding sulfonated two-dimensional porous material (COFs-SO3H) to the aqueous phase of polyamine reacts with the acyl chloride structure in the organic phase to form an aldehyde-amine condensation reaction, generating a network structure. The sulfonated two-dimensional porous material (COFs-SO3H) simultaneously provides an acid-resistant framework structure and sulfonyl acid-resistant groups. The resulting polysulfonamide acid-resistant nanofiltration membrane has low membrane flux and suffers from problems such as uneven dispersion of the sulfonated two-dimensional porous material, which affects membrane performance.
[0026] Furthermore, interlayer thin-film nanocomposite membranes (TFNi) with added nanomaterials as an intermediate layer are an emerging type of composite membrane, showing significant potential in terms of permeability-selectivity compared to conventional thin-film composite (TFC) nanofiltration membranes. The nanomaterial intermediate layer can optimize water transport pathways, regulate the diffusion-reaction of aqueous monomers during interfacial polymerization, and achieve controllable adjustment of the pore size, charge, and thickness of the separation layer, thereby improving the permeation and separation performance of the nanofiltration membrane. Based on this, this invention provides a high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane, its preparation method, and its application. By introducing an intermediate layer of functionally modified mesoporous SiO2 nanoparticles between the base membrane and the separation layer, the polysulfonamide acid-resistant nanofiltration membrane possesses the advantages of high flux, high rejection rate, and acid resistance. Specific implementation methods are as follows: In a first aspect, the present invention provides a high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane, comprising a base membrane and a separation layer, and further comprising an intermediate layer located between the base membrane and the separation layer; the intermediate layer comprises functionally modified mesoporous SiO2 nanoparticles; wherein... The functional group-modified mesoporous SiO2 nanoparticles are selected from amino-modified mesoporous SiO2 nanoparticles, and / or mesoporous SiO2 nanoparticles co-modified with amino and trifluoropropyl groups.
[0027] In specific implementation, the present invention modifies the surface functional groups of mesoporous SiO2 nanoparticles to make them rich in amino groups, thereby providing more reaction binding sites and higher charge on the intermediate layer formed by the subsequent bonding of mesoporous SiO2 nanoparticles with the base film (hydrophilic base film); and improving the adhesion between the intermediate layer and the support layer and the separation layer.
[0028] Secondly, functionally modified mesoporous SiO2 nanoparticles, acting as an interlayer, can significantly alter the surface charge of the nanofiltration membrane, improving its rejection rate for divalent cations and its selectivity for separating monovalent and high-valent ions. Based on the mesoporous structure of the mesoporous SiO2 nanoparticles, this interlayer provides additional water channels, increasing the membrane's permeation flux and compensating for the low permeation flux of polysulfonamide nanofiltration membranes. Simultaneously, the mesoporous SiO2 nanoparticles themselves are highly stable in acidic environments and are not easily corroded or dissolved. The interlayer they form can also hinder the permeation path of acidic media, delaying acid erosion of the membrane substrate and improving the membrane's acid resistance. Furthermore, the presence of acid-resistant fluorinated groups on the nanoparticles not only effectively inhibits aggregation between nanoparticles but also provides even higher acid resistance, thus constructing a stable composite membrane.
[0029] In some embodiments, the amino-modified mesoporous SiO2 nanoparticles used in this invention are obtained by the following preparation method: Mesoporous SiO2 nanoparticles were dispersed in an ammonia solution and mixed with a 1-10 wt% solution of 3-aminopropyltriethoxysilane. After ultrasonic stirring for 8-12 h, the solid particles were separated, washed, and dried to obtain amino-modified mesoporous SiO2 nanoparticles.
[0030] It should be noted that the surface of mesoporous SiO2 nanoparticles contains abundant silanol groups. Under alkaline conditions provided by ammonia solution, 3-aminopropyltriethoxysilane (APTES) covalently bonds with the hydroxyl groups on the SiO2 surface, introducing amino (-NH2) functional groups. In addition, the surface of mesoporous SiO2 nanoparticles is negatively charged in an alkaline environment, which enhances the electrostatic repulsion between mesoporous SiO2 nanoparticles and can effectively alleviate the uneven modification caused by the aggregation of mesoporous SiO2 nanoparticles during the amino modification process.
[0031] In some embodiments, the mesoporous SiO2 nanoparticles co-modified with amino and trifluoropropyl groups used in this invention are obtained by the following preparation method: Mesoporous SiO2 nanoparticles were dispersed in an ammonia solution, and 3-aminopropyltriethoxysilane and 3,3,3-trifluoropropyltrimethoxysilane were added. After mixing evenly, the mixture was reacted at 60-80 °C for 8-12 h. The solid particles were separated, washed, and dried to obtain mesoporous SiO2 nanoparticles modified with amino and trifluoropropyl groups.
[0032] In an alkaline environment, 3-aminopropyltriethoxysilane and 3,3,3-trifluoropropyltrimethoxysilane undergo co-condensation with the hydroxyl groups on the surface of mesoporous SiO2 nanoparticles, simultaneously grafting the hydrophilic amino group (-NH2) and the hydrophobic trifluoropropyl group onto the surface of the mesoporous SiO2 nanoparticles; the mass ratio of 3-aminopropyltriethoxysilane to 3,3,3-trifluoropropyltrimethoxysilane used in the reaction is 1:1.
[0033] It should be noted that the mesoporous SiO2 nanoparticles used in this invention can be commercially available or obtained through the following synthesis route: Dissolve hexadecyltrimethylammonium bromide in an aqueous ethanol solution to form a mixed solution, and adjust the pH to 10-11 by adding ammonia dropwise; Tetraethyl orthosilicate was slowly added dropwise to the mixed solution. After stirring for 2-4 h, trimethylbenzene was added and the reaction continued for 1-2 h. The resulting emulsion was refluxed with acidic ethanol for 10-12 h. The particles collected by centrifugation were washed and vacuum dried to obtain the mesoporous SiO2 nanoparticles.
[0034] In some embodiments, the composition of the base film used in this invention is selected from polyethylene, polypropylene, or polyacrylonitrile; the composition of the separation layer is polysulfonamide.
[0035] In specific implementation, the separation layer of the acid-resistant nanofiltration membrane provided by the present invention is composed of polysulfonamide, which has better acid resistance and oxidation resistance than commonly used polyamide; this lays the foundation for the acid resistance of the entire membrane, and the addition of the intermediate layer further enhances this advantage.
[0036] Secondly, the present invention provides a method for preparing the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane described in the first aspect above. Figure 1 A flowchart illustrating the preparation method of the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane provided by the present invention is shown, as follows: Figure 1 As shown, the preparation method includes the following steps: S1. Place the base membrane in NaOH solution and soak for 2-4 hours. Then, transfer it to the activation solution and treat for 1-2 hours to obtain a hydrophilic base membrane. In specific implementation, the mass fraction of NaOH solution is 10-15%. This step uses alkaline solution immersion to modify the surface of the base film with free hydroxyl groups. Then, the base film is transferred to the activation solution for activation treatment to obtain a hydrophilic base film. The presence of hydroxyl groups in the base film provides binding sites for the binding of strongly functionalized mesoporous SiO2 nanoparticles to the base film, thereby improving the adhesion between the intermediate layer, support layer, and separation layer.
[0037] In some embodiments, the activation solution comprises trifluoroethanesulfonic anhydride and anhydrous pyridine, with anhydrous dichloromethane as the solvent, and the concentrations of trifluoroethanesulfonic anhydride and anhydrous pyridine are 0.1 M. The activation treatment can induce nucleophilic substitution of hydroxyl and amino groups, lowering the reaction energy barrier and providing attack activation sites for the amino group.
[0038] S2. Disperse functional group-modified mesoporous SiO2 nanoparticles in N,N-dimethylformamide to form a dispersion; bring one side of the hydrophilic base membrane into contact with the dispersion, so that the functional groups on the surface of the functional group-modified mesoporous SiO2 nanoparticles undergo a nucleophilic substitution reaction with the activated hydroxyl groups on the surface of the hydrophilic base membrane, and are fixed to the surface of the hydrophilic base membrane. After drying, a polysulfonamide acid-resistant nanofiltration membrane intermediate is obtained. In this specific step, the concentration of functionally modified mesoporous SiO2 nanoparticles in the dispersion is 0.1~5wt%. When the hydrophilic base film comes into contact with the dispersion, the amino groups (-NH2) modified on the surface of the mesoporous SiO2 nanoparticles in the dispersion combine with the activated hydroxyl groups on the surface of the hydrophilic base film, thereby stably fixing the mesoporous SiO2 nanoparticles on the surface of the base film. The contact reaction time between the hydrophilic base film and the dispersion is 2-6 h.
[0039] S3. The surface of the intermediate with the functional group-modified mesoporous SiO2 nanoparticles fixed on it is brought into contact with an aqueous phase containing an organic amine and an organic phase containing an organic sulfonyl chloride, respectively. Through interfacial polymerization, a separation layer is formed on the surface of the intermediate, thus completing the preparation of the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane.
[0040] In specific implementation, one side of the base membrane surface with functionalized mesoporous SiO2 nanoparticles is further contacted with an aqueous phase containing an organic amine and an organic phase containing an organosulfonyl chloride. Through interfacial polymerization, a separation layer is formed on the surface of the intermediate. The concentration of the organic amine in the aqueous phase is 0.5 wt% to 3.5 wt%, and the organic amine is selected from polyethyleneimine and / or polyacrylamine. The concentration of the organosulfonyl chloride in the organic phase is 0.1 wt% to 0.3 wt%, and the organosulfonyl chloride is selected from at least one of 1,3,5-benzenetrisulfonyl chloride, 1,3,6-naphthalenetrisulfonyl chloride, and isophenylene disulfonyl chloride. This invention constructs a polysulfonamide acid-resistant nanofiltration membrane with high acid resistance through the synergistic effect of functionalized mesoporous SiO2 nanoparticle bridging and interfacial polymerization.
[0041] In some embodiments, the side of the base film surface with functional group-modified mesoporous SiO2 nanoparticles is first contacted with an aqueous phase containing amine monomers for 2-10 minutes and then removed, followed by contact with an organic phase containing sulfonyl chloride for 30 seconds to 3 minutes. This completes the interfacial polymerization reaction and forms a separation layer.
[0042] Thirdly, the present invention provides an application of the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane described in the first aspect above, wherein the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane is used as a membrane material for membrane separation and recovery of precious metals in acidic wastewater.
[0043] To enable those skilled in the art to more clearly understand the present invention, the following embodiments are provided to illustrate in detail the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane and its preparation method.
[0044] (1) Preparation of mesoporous SiO2 nanoparticles A: Dissolve hexadecyltrimethylammonium bromide (CTAB) in deionized water and ethanol (volume ratio 16:1), stir at 60°C until completely dissolved, add ammonia water (28 wt%) dropwise, and adjust the pH to 10-11; B: Slowly add tetraethyl orthosilicate (TEOS) dropwise to the solution obtained in step A, stir and react at 60 °C (600 rpm) for 2 hours, then continue to add trimethylbenzene (TMB) and continue to react for 1 hour; C: The emulsion obtained in step B was refluxed with acidic ethanol (HCl / ethanol, 1:50 v / v) for 12 h, the particles were collected by centrifugation (10000 rpm, 15 min), washed 3 times with ethanol / water, and vacuumed at 60 °C for 24 h to obtain mesoporous SiO2 nanoparticles (HMONS).
[0045] (2) Preparation of amino-modified mesoporous SiO2 nanoparticles The obtained mesoporous SiO2 nanoparticles were uniformly dispersed in an ammonia solution and mixed with 0.1 wt% 3-aminopropyltriethoxysilane (APTES). After ultrasonic stirring for 12 h, the solid particles separated by centrifugation were repeatedly washed with ethanol and water. This process was repeated 3-4 times. After drying, amino-modified mesoporous SiO2 nanoparticles (HMON) were obtained. S -NH2).
[0046] (3) Preparation of mesoporous SiO2 nanoparticles co-modified with amino and trifluoropropyl groups The obtained mesoporous SiO2 nanoparticles were uniformly dispersed in an ammonia solution, and 3-aminopropyltriethoxysilane (APTES) and 3,3,3-trifluoropropyltrimethoxysilane (TFPTMS) were added; wherein the mass concentration of 3-aminopropyltriethoxysilane (APTES) was 0.1 wt%, and the mass concentration of 3,3,3-trifluoropropyltrimethoxysilane (TFPTMS) was 0.1 wt%; after mixing evenly, the mixture was reacted at 60-80 ℃ for 8-12 h. The solid particles separated by centrifugation were repeatedly washed with ethanol and water, and the above operation was repeated 3-4 times. After drying, mesoporous SiO2 nanoparticles (C3H4F) modified with amino and trifluoropropyl groups were obtained. 3- HMON S -NH2).
[0047] (4) Hydrophilic treatment of the base membrane The polyethylene film (PE film), polypropylene film, or polyacrylonitrile film was placed in a 15% NaOH solution for 4 hours of alkaline treatment. Then, the base film was immersed in an activation solution (containing 0.1 M trifluoroethanesulfonic anhydride, anhydrous pyridine, and anhydrous dichloromethane as solvent) at 25°C for 1 hour. After that, it was taken out, rinsed three times with anhydrous dichloromethane, and dried for later use.
[0048] (5) Preparation of the intermediate layer HMONS, HMONS-NH2 or / and C3H4F3-HMONS-NH2 are dispersed in DMF to prepare a dispersion with a concentration of 0.1~1 wt%. One side of the hydrophilic base membrane prepared in step (4) is placed in the dispersion to allow the functional group modified mesoporous SiO2 nanoparticles to be bonded to the surface of the hydrophilic base membrane. After 120 min, it is taken out and dried to obtain a polysulfonamide acid-resistant nanofiltration membrane intermediate containing an intermediate layer. (6) Preparation of separation layer Further, the intermediate obtained in step (5) with functional group-modified mesoporous SiO2 nanoparticles fixed on the surface is fixed on a glass plate with one side facing upward, and contacted with an aqueous solution for 1 min; after removing excess water, it is then contacted with an organic phase solution for 0.5 min, and a polysulfonamide composite layer is obtained through interfacial polymerization reaction; wherein, the aqueous phase contains an organic amine, which is selected from polyethyleneimine (PEI) and / or polyacrylamide (PAA), with a concentration of 1 wt%; the organic phase contains an organic sulfonyl chloride, which is selected from at least one of 1,3,5-benzenetrisulfonyl chloride, 1,3,6-naphthalenetrisulfonyl chloride and isophenyl disulfonyl chloride, with a concentration of 0.2 wt%.
[0049] Specific implementation details are shown in Table 1: Table 1. Statistical analysis of preparation conditions for each example and comparative example.
[0050] Note: Steps (1), (2), (3), and (5) above are not performed for Comparative Example 1, and step (4) above is not performed for Comparative Examples 2 and 3.
[0051] The polysulfonamide acid-resistant nanofiltration membrane prepared in Example 3 was characterized and tested. Figure 2 The image shows a surface electron microscope (SEM) image (left) and a cross-sectional electron microscope (SEM) image (right) of a polysulfonamide acid-resistant nanofiltration membrane, as shown. Figure 2 As shown in the image, the surface electron microscope image (left) of the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane shows that PAA reacts with 1,3,5-benzenetrisulfonyl chloride to form a dense separation layer, while the separation layer thickness is only 28 nm (right image), which enables the polysulfonamide acid-resistant nanofiltration membrane provided by the present invention to maintain a high rejection rate while having a high permeation flux.
[0052] Figure 3 An electron micrograph of the intermediate layer of a high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane is shown, as follows: Figure 3 As shown, uniformly sized, single-layered, densely packed spherical C3H4F3-HMONs-NH2 nanoparticles are firmly grafted onto a hydrophilic PE membrane.
[0053] Figure 4 Transmission electron microscopy (TEM) images of high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membranes are shown, such as... Figure 4 As shown, the polysulfonamide separation layer is formed on the polysulfonamide acid-resistant nanofiltration membrane intermediate containing the intermediate layer and the separation layer thickness is 28 nm. Performance testing Single-component salt solutions of LiCl, CoCl3, and MnCl2 with a concentration of 1.0 g / L were used as filter media to test the permeation flux and retention rate performance of the nanofiltration membranes prepared in the above examples and comparative examples.
[0054] In practice, the separation performance of the nanofiltration membrane is measured using a cross-flow filtration device. To ensure a stable permeate flux, the nanofiltration membrane is first pre-pressurized at 0.2 MPa for 1 hour, and then the permeate volume is collected at regular intervals at 0.2 MPa. The formula for calculating the pure permeate flux is as follows:
[0055] Where P represents pure permeation flux, in L·m -2 ·h -1 ·bar -1 ΔV represents the volume of filtrate during the filtration time, in liters (L); A represents the filtration area, in square meters (m²). 2 Δt represents the filtration time in hours (h); Δp represents the application pressure in bars.
[0056] The rejection rate test method is as follows: A single-component salt solution of 1.0 g / L LiCl is used to test the Li content of the NF membrane. + The rejection rate was tested. Before the experiment, the membrane was pre-pressurized for 1 h at a pressure of 0.2 MPa and a flow rate of 3 LPM. After the flux stabilized, the separation performance was tested under the same conditions.
[0057] The formula for calculating the rejection rate is as follows:
[0058] Where R represents the retention rate (%); C f This represents the concentration of the solute in the feed solution. C p Represents the concentration of the solute in the permeate (g·L) -1 For single-component salt solutions, the concentration of the single electrolyte in the solution is linearly related to the conductivity of the solution; therefore, C p / C f The conductivity of the permeate and feed liquid was measured separately using a conductivity meter, and then the conductivity ratio was used for equivalent calculation. The test results are shown in Table 2: Table 2. Performance of nanofiltration membranes prepared in each example and comparative example.
[0059] As shown in Table 2, the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membranes prepared in Examples 1-6 have a permeation flux of 20 L·m⁻¹. -2 ·h -1 ·bar -1 Furthermore, with the increase of C3H4F3-HMONs-NH2 concentration, the permeation flux of the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane continuously increases, and the rejection rate of the tested salts also increases accordingly. When the concentration increases to 0.6 wt%, the permeation flux reaches its maximum value of 30.50 L·m⁻¹. -2 ·h -1 ·bar -1 The rejection rates for CoCl3 and MnCl2 reached 99.8% and 97.8%, respectively.
[0060] The nanofiltration membranes provided in Examples 3, 7, 8, and Comparative Example 1 were further subjected to acid treatment with 20 wt% H2SO4 for 30 days, and then the permeate flux and rejection rate performance tests were performed as described above. The test results are shown in Table 3. Table 3. Performance of nanofiltration membranes prepared in the examples and comparative examples after acid treatment.
[0061] As shown in Table 3, the flux of the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane prepared in Example 3 after treatment with 20 wt% H2SO4 for 30 days is 25.25 L·m. -2 ·h -1 ·bar -1 The highest rejection rates for CoCl3 and MnCl2 were observed in Examples 3, 7, and 8, which used HMONs or HMONs-NH2 as the intermediate layer. The rejection rates for CoCl3 and MnCl2 were moderate. The rejection rates for CoCl3 and MnCl2 of the acid-resistant nanofiltration membrane in Comparative Example 1, which did not have an intermediate layer, were lower than those of Examples 3, 7, and 8.
[0062] Therefore, the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane provided by the present invention has the characteristics of high rejection rate of divalent cations, high water permeability and excellent acid resistance, and is suitable for the field of membrane separation technology.
[0063] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. In addition, those skilled in the art can combine and integrate the different embodiments or examples described in this specification.
[0064] For the sake of simplicity, the method embodiments are described as a series of actions. However, those skilled in the art should understand that the present invention is not limited to the described order of actions, as some steps can be performed in other orders or simultaneously according to the present invention. Furthermore, those skilled in the art should also understand that the embodiments described in the specification are preferred embodiments, and the actions and components involved are not necessarily essential to the present invention.
[0065] The above provides a detailed description of a high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane, its preparation method, and its applications. Specific examples have been used to illustrate the principles and implementation methods of the invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the invention. Therefore, the content of this specification should not be construed as a limitation of the invention.
Claims
1. A high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane, comprising a base membrane and a separation layer, characterized in that, It also includes an intermediate layer located between the base film and the separation layer; the intermediate layer comprises functionally modified mesoporous SiO2 nanoparticles; wherein, The functional group-modified mesoporous SiO2 nanoparticles are selected from amino-modified mesoporous SiO2 nanoparticles, and / or mesoporous SiO2 nanoparticles co-modified with amino and trifluoropropyl groups.
2. The high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane according to claim 1, characterized in that, The amino-modified mesoporous SiO2 nanoparticles were obtained by the following preparation method: Mesoporous SiO2 nanoparticles were dispersed in an ammonia solution and mixed with a 1-10 wt% solution of 3-aminopropyltriethoxysilane. After ultrasonic stirring for 8-12 h, the solid particles were separated, washed, and dried to obtain amino-modified mesoporous SiO2 nanoparticles.
3. The high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane according to claim 1, characterized in that, The mesoporous SiO2 nanoparticles co-modified with amino and trifluoropropyl groups were obtained by the following preparation method: Mesoporous SiO2 nanoparticles were dispersed in an ammonia solution, and 3-aminopropyltriethoxysilane and 3,3,3-trifluoropropyltrimethoxysilane were added. After mixing evenly, the mixture was reacted at 60-80 °C for 8-12 h. The solid particles were separated, washed, and dried to obtain mesoporous SiO2 nanoparticles modified with amino and trifluoropropyl groups.
4. The high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane according to claim 1, characterized in that, The composition of the base film is selected from polyethylene, polypropylene, or polyacrylonitrile; The separation layer is composed of polysulfonamide.
5. A method for preparing a high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane according to any one of claims 1-4, characterized in that, The preparation method includes the following steps: The base membrane was placed in NaOH solution and soaked for 2-4 hours, then transferred to an activation solution for 1-2 hours to obtain a hydrophilic base membrane. Functionally modified mesoporous SiO2 nanoparticles are dispersed in N,N-dimethylformamide to form a dispersion. One side of the hydrophilic base membrane is brought into contact with the dispersion, so that the functional groups on the surface of the functionally modified mesoporous SiO2 nanoparticles undergo a nucleophilic substitution reaction with the activated hydroxyl groups on the surface of the hydrophilic base membrane, and are fixed to the surface of the hydrophilic base membrane. After drying, a polysulfonamide acid-resistant nanofiltration membrane intermediate is obtained. One side of the intermediate with the functional group-modified mesoporous SiO2 nanoparticles fixed on its surface is contacted with an aqueous phase containing an organic amine and an organic phase containing an organic sulfonyl chloride, respectively. Through interfacial polymerization, a separation layer is formed on the surface of the intermediate, thus completing the preparation of the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane. The activation solution comprises trifluoroethanesulfonic anhydride and anhydrous pyridine, with anhydrous dichloromethane as the solvent, and the concentration of the trifluoroethanesulfonic anhydride and anhydrous pyridine is 0.1M.
6. The method for preparing the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane according to claim 5, characterized in that, In the dispersion, the concentration of the functional group-modified mesoporous SiO2 nanoparticles is 0.1~5wt%.
7. The method for preparing the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane according to claim 5, characterized in that, The organic amine is selected from polyethyleneimine and / or polyacrylamide, and the concentration of the organic amine in the aqueous phase is 0.5wt% to 3.5wt%.
8. The method for preparing the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane according to claim 5, characterized in that, The organic sulfonyl chloride is selected from at least one of 1,3,5-benzenetrisulfonyl chloride, 1,3,6-naphthalenetrisulfonyl chloride and m-benzenedisulfonyl chloride, and the concentration of the organic sulfonyl chloride in the organic phase is 0.1wt% to 0.3wt%.
9. The method for preparing the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane according to claim 5, characterized in that, The mesoporous SiO2 nanoparticles are obtained through the following method: Dissolve hexadecyltrimethylammonium bromide in a mixed solution of deionized water and ethanol, and adjust the pH to 10-11 by adding ammonia dropwise; Tetraethyl orthosilicate was slowly added dropwise to the mixed solution. After stirring for 2-4 h, trimethylbenzene was added and the reaction continued for 1-2 h. The resulting emulsion was refluxed with acidic ethanol for 10-12 h. The particles collected by centrifugation were washed and vacuum dried to obtain the mesoporous SiO2 nanoparticles.
10. An application of the high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane according to any one of claims 1-4, characterized in that, The high-performance mesoporous silica / polysulfonamide acid-resistant nanofiltration membrane is used as a membrane material for the membrane separation and recovery of precious metals in acidic wastewater.
Citation Information
Patent Citations
Mesoporous silicon dioxide sphere-polymer nano composite nano-filtration membrane and preparation method thereof
CN102794116A
Preparation method of positively charged acid-resistant nano composite nanofiltration membrane
CN117379990A
Preparation method of anti-fouling and acid-resistant nanofiltration membrane applied to high-salinity water
CN118807463A